PERAN LINGKUNGAN BELAJAR DAN SELF EFFICACY TERHADAP COLLEGE STUDENT SUBJECTIVE WELL-BEING - Randi Mursandi; Asri Mutriara Putri; Vira Sandayanti (Program Studi Psikologi Universitas Malahayati, 2022)
ABSTRACT: THE ROLE OF THE LEARNING ENVIRONMENT AND SELF EFFICACY ON COLLEGE STUDENT SUBJECTIVE WELL BEING College student subjective well-being is a new concept developed by Renshaw about assessing the quality of life of individuals in college. College student subjective well-being can be influenced by environmental factors (learning environment), demographic factors, and personality factors (self-efficacy). This research aims to find out the role of learning environments and self-efficacy on college student subjective well-being. The subjects in this study were 400 undergraduate students who studied in Bandar Lampung (151 male students and 249 female students), with a convenience sampling technique. The data collection uses the College Student Subjective Well-being Questionnaire (CSSWQ), Dundee Ready Educational Environment Measure (DREEM), and General Self-efficacy Scale (GSE). The data collected in the analysis uses multiple regression analysis techniques. The results of the analysis showed that there is a role between the learning environment and self-efficacy on the college student subjective well-being, this shows that the learning environment and self-efficacy play an important role in improving the subjective well-being of students. Therefore, the learning and self-efficacy environment needs more attention, be it from universities, parents and students themselves to improve the state of college student subjective well-being. Keywords: College Student Subjective Well-Being, Learning Environment, Self-Efficacy. College student subjective well-being adalah konsep baru yang dikembangkan oleh Renshaw tentang penilaian kualitas hidup individu pada perguruan tinggi. College student subjective well-being bisa di pengaruhi oleh faktor lingkungan (lingkungan belajar), faktor demografi dan faktor kepribadian (self-efficacy). Penelitian ini bertujuan untuk mengetahui peran lingkungan belajar dan self-efficacy terhadap college student subjective well-being. Subjek dalam penelitian ini adalah 400 orang mahasiswa S1 yang berkuliah di Bandar Lampung (151 mahasiswa laki-laki dan 249 mahasiwa perempuan), dengan teknik sampling Convenience Sampling. Pengumpulan data menggunakan College Student Subjective Well-being Questionnaire (CSSWQ), Dundee Ready Educational Environment Measure (DREEM) dan General Self-efficacy Scale (GSE). Data yang terkumpul di analisis menggunakan teknik analisis regresi berganda. Hasil analisis menunjukkan bahwa adanya peran antara lingkungan belajar dan self-efficacy terhadap college student subjective well-being, Hal ini menunjukkan bahwa lingkungan belajar dan self-efficacy berperan penting dalam meningkatkan subjective well-being mahasiswa. Oleh karena itu lingkungan belajar dan self-efficacy perlu mendapat perhatian yang lebih, baik itu dari universitas, orang tua dan mahasiswa itu sendiri dalam upaya meningkatkan keadaan college student subjective well-being. Kata Kunci: College Student Subjective Well-Being, Lingkungan Belajar, Self-Efficacy